POLA KOMUNIKASI HATESPEECH DAN CYBERBULLYING DI MEDIA SOSIAL - rama wijaya kesuma wardani; Marisa Deza Febriyeni; Nurlila Kamsi (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2020)
This article explains how ethics communicates on social media in the eyes of Islam. Advances in technology and speed in accessing current information make the community enthusiastic in using gadgets with social media applications such as Facebook, Instagram, line, Twitter and other applications. Many positive impacts that we can take from these social media applications such as obtaining information, creating relationships and others. The emergence of hoaxes and cyberbullying is a social media. The current phenomenon, a number of hate speech on religious sentiment, the critical theory of Jurgen Habermas who is about to penetrate reality through his critical theory as a sociological fact, to find a transcsedative condition that transcends Empirical data. The rise of Hatespeech and cyberbullying is social, so we need ethics in order to be able to use social media by bringing benefits to others